Pengembangan Media Video Pembelajaran pada Mata Pelajaran Sejarah Kebudayaan Islam untuk Siswa Kelas VII MTSN - Fauzi, Ahmad; Hidayati, Abna; Syafril, Syafril; Novrianti, Novrianti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to produce learning video media for SKI Class VII MTsN subjects that are valid and practical. This type of research is development research, known as Research and Development (R&D), using the 4-D development model. The development procedure in this research consists of 4 stages, namely, (1) Define, (2) Design, (3) Develop, (4) Disseminate. The product validity test was carried out by 3 validators, namely 1 material validator and 2 media validators. Product trials were carried out on class VII students at MTsN 5 Tanah Datar with the aim of finding out the practicality of the product being developed. The results of material validation by material expert validators obtained an average of 4.94 in the